Japanese politeness : an enquiry - Obana, Yasuko (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Although Japanese language is one of the most quoted examples in politeness research, extant publications focus on particular areas of politeness, and very few of them enquire into varied aspects of Japanese politeness. In this book, Yasuko Obana provides an integrated account of what signifies Japanese politeness. She also carves out politeness strategies in Japanese, which have not adequately been explored to date in spite of their distinctive nature that they often reflect social indexicality just as honorifics."--
OCLC-licensed vendor bibliographic record.
Keywords: Politeness (Linguistics); Japanese language -- Semantics; Japanese language -- Honorific; FOREIGN LANGUAGE STUDY / Japanese; LANGUAGE ARTS & DISCIPLINES / Journalism